2016
DOI: 10.2106/jbjs.o.00334
|View full text |Cite
|
Sign up to set email alerts
|

Passive Hip Range of Motion Predicts Femoral Torsion and Acetabular Version

Abstract: This study confirmed that passive hip range of motion significantly predicts combined femoral torsion and central acetabular version. Accurate clinical assessment of the COTAV index may inform surgical decision-making in hip preservation surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 46 publications
4
113
0
6
Order By: Relevance
“…Recently Chadayammuri et al reported decreased degree of hip exion (mean 104 0 ) with acetabular retroversion with no effect of femoral torsion [7]. At an anatomic study of ischio-femoral impingement model with concamittant decrease of terminal hip extension, Gomes-Hoyos et al reported increase of the L3-4 and L4-5 lumbar facet joint load [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Chadayammuri et al reported decreased degree of hip exion (mean 104 0 ) with acetabular retroversion with no effect of femoral torsion [7]. At an anatomic study of ischio-femoral impingement model with concamittant decrease of terminal hip extension, Gomes-Hoyos et al reported increase of the L3-4 and L4-5 lumbar facet joint load [6].…”
Section: Discussionmentioning
confidence: 99%
“…Both femoral anteversion , acetabular antversion abnormalities have been described in pathogenesis of hip osteoarthritis [7][8][9][10][11][12]15] and hip osteoarthritis is being linked to lumbar spine disease. However; none of study in the literature directly searched causal relationship of these parameters at lumbar disc disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical tests were all performed by one of three staff hip surgeons. The internal hip rotation was assessed in the sitting position with a goniometer, and the impingement test was performed in the supine position . Inclusion age was 20–50 years.…”
Section: Methodsmentioning
confidence: 99%
“…Previous study has indicated a significant association between internal rotation range of motion and femoral anteversion [10]. Crane found that children with increased femoral anteversion angle had internal rotation of the hip exceeding 60° [5].…”
Section: Introductionmentioning
confidence: 99%